Literatur Review: Financial Recovery Post Covid 19 - Ani Maryani; Rindy Dwi Ladista; Irwandi (PT. Altaf Publishing Corp, 2025)
The purpose of this study is to identify strategic steps for restoring a company's financial condition using a turnaround proxy approach. The COVID-19 crisis significantly affected corporate financial performance, causing many companies to experience financial distress and operational decline, thus requiring effective recovery strategies. This study employs a descriptive qualitative approach supported by statistical analysis to understand the phenomena that occurred during the pandemic and to analyze the implementation of turnaround strategies in the financial recovery process. The findings reveal that financial recovery efforts are directed at reversing loss conditions into profitability through cost-efficiency and restructuring measures, including (1) freeing non-productive or idle assets, (2) reducing or divesting underperforming assets, and (3) implementing restructuring strategies to address the severity of financial distress.